Two adjacent inversions maintain genomic differentiation between migratory and stationary ecotypes of Atlantic cod. Issue 10 (20th April 2016) - Kirubakaran, Tina Graceline; Grove, Harald; Kent, Matthew P.; Sandve, Simen R.; Baranski, Matthew; Nome, Torfinn; De Rosa, Maria Cristina; Righino, Benedetta; Johansen, Torild; Otterå, Håkon; Sonesson, Anna; Lien, Sigbjørn; et al.
Abstract: Atlantic cod is composed of multiple migratory and stationary populations widely distributed in the North Atlantic Ocean. The Northeast Arctic cod (NEAC) population in the Barents Sea undertakes annual spawning migrations to the northern Norwegian coast. Although spawning occurs sympatrically with the stationary Norwegian coastal cod (NCC), phenotypic and genetic differences between NEAC and NCC are maintained. In this study, we resolve the enigma by revealing the mechanisms underlying these differences. Extended linkage disequilibrium (LD) and population divergence were demonstrated in a 17.4‐Mb region on linkage group 1 (LG1) based on genotypes of 494 SNPs from 192 parents of farmed families of NEAC, NCC or NEACxNCC crosses. Linkage analyses revealed two adjacent inversions within this region that repress meiotic recombination in NEACxNCC crosses. We identified a NEAC‐specific haplotype consisting of 186 SNPs that was fixed in NEAC sampled from the Barents Sea, but segregating under Hardy–Weinberg equilibrium in eight NCC stocks. Comparative genomic analyses determine the NEAC configuration of the inversions to be the derived state and date it to 1.6–2.0 Mya. The haplotype block harbours 763 genes, including candidates regulating swim bladder pressure, haem synthesis and skeletal muscle organization conferring adaptation to long‐distance migrations and vertical movements down to large depths. Our results suggest that the migratory ecotype experiences strong directional selection for the two adjacent inversions on LG1. Despite interbreeding between NEAC and NCC, the inversions are maintaining genetic differentiation, and we hypothesize the co‐occurrence of multiple adaptive alleles forming a 'supergene' in the NEAC population. Abstract : See also the Perspective by Samuk